2022
DOI: 10.3390/antiox11040787
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Anesthesia and Oxidative Stress

Abstract: Neonatal anesthesia, while often essential for surgeries or imaging procedures, is accompanied by significant risks to redox balance in the brain due to the relatively weak antioxidant system in children. Oxidative stress is characterized by concentrations of reactive oxygen species (ROS) that are elevated beyond what can be accommodated by the antioxidant defense system. In neonatal anesthesia, this has been proposed to be a contributing factor to some of the negative consequences (e.g., learning deficits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 215 publications
0
8
0
Order By: Relevance
“…Both sevoflurane and propofol have been shown to inhibit proinflammatory cytokine release and OSI. 20 - 21 Some investigators have compared the protective effects of sevoflurane and propofol on inflammation and OSI, but the results are contradictory. It is demonstrated that propofol but not sevoflurane prevents OSI in hepatic ischemia/reperfusion injury, 22 while Xie et al 23 illustrated that sevoflurane exerts greater protective effects than propofol on hypoxia-reoxygenation injury in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both sevoflurane and propofol have been shown to inhibit proinflammatory cytokine release and OSI. 20 - 21 Some investigators have compared the protective effects of sevoflurane and propofol on inflammation and OSI, but the results are contradictory. It is demonstrated that propofol but not sevoflurane prevents OSI in hepatic ischemia/reperfusion injury, 22 while Xie et al 23 illustrated that sevoflurane exerts greater protective effects than propofol on hypoxia-reoxygenation injury in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Both sevoflurane and propofol have been shown to inhibit proinflammatory cytokine release and OSI. [20][21] Some investigators have compared the protective effects of sevoflurane and propofol on inflammation and OSI, but the results are contradictory.…”
Section: Regulation Of Sevoflurane and Propofol On Macrophage Lncrna-...mentioning
confidence: 99%
“…The interference with normal maturation processes early in development may affect NOS interneuron neurovascular interactions to a greater degree, while insults later in development may be more targeted toward VIP- and SST-mediated mechanisms of oxygen regulation. Importantly, these differences in development also point to age-related pathological onset of various psychiatric disorders, such as schizophrenia and anxiety disorders ( Kim-Cohen et al, 2003 ; Dalsgaard et al, 2020 ; Collins and Ninan, 2021 ), as well as the development of learning deficits following neonatal anesthesia exposure ( Gascoigne et al, 2021 , 2022 ). Research in this field is ongoing and will likely be able to address interneuron subtype specific contributions to a range of pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…This age was chosen based on previous literature outlining the timing of adolescence in rodents. Postnatal day (PND [25][26][27][28][29][30] marks the beginning of early adolescence in male and female rats, while PND 60-70 marks the beginning of early adulthood 23,24 . Seventy-two pre-adolescent male and female Wistar rats from eight mothers were randomly assigned to the experimental or control groups.…”
Section: Methods and Materials Animalmentioning
confidence: 99%